Calcium Signaling Properties of a Thyrotroph Cell Line, Mouse T?T1 Cells - Leiva-Salcedo, D (Churchill Livingstone, 2015)
TαT1 cells are mouse thyrotroph cell line frequently used for studies on thyroid-stimulating hormone beta subunit gene expression and other cellular functions. Here we have characterized calcium-signaling pathways in TαT1 cells, an issue not previously addressed in these cells and incompletely described in native thyrotrophs. TαT1 cells are excitable and fire action potentials spontaneously and in response to application of thyrotropin-releasing hormone (TRH), the native hypothalamic agonist for thyrotrophs. Spontaneous electrical activity is coupled to small amplitude fluctuations in intracellular calcium, whereas TRH stimulates both calcium mobilization from intracellular pools and calcium influx. Non-receptor-mediated depletion of intracellular pool also leads to a prominent facilitation of calcium influx. Both receptor and non-receptor stimulated calcium influx is substantially attenuated but not completely abolished by inhibition of voltage-gated calcium channels, suggesting that depletion of intracellular calcium pool in these cells provides a signal for both voltage-independent and -dependent calcium influx, the latter by facilitating the pacemaking activity. These cells also express purinergic P2Y1 receptors and their activation by extracellular ATP mimics TRH action on calcium mobilization and influx. The thyroid hormone triiodothyronine prolongs duration of TRH-induced calcium spikes during 30-min exposure. These data indicate that TαT1 cells are capable of responding to natively feed-forward TRH signaling and intrapituitary ATP signaling with acute calcium mobilization and sustained calcium influx. Amplification of TRH-induced calcium signaling by triiodothyronine further suggests the existence of a pathway for positive feedback effects of thyroid hormones probably in a non-genomic manner. © 2015 Elsevier Ltd.